-4(3y+2)=3(6y-6)

Simple and best practice solution for -4(3y+2)=3(6y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3y+2)=3(6y-6) equation:


Simplifying
-4(3y + 2) = 3(6y + -6)

Reorder the terms:
-4(2 + 3y) = 3(6y + -6)
(2 * -4 + 3y * -4) = 3(6y + -6)
(-8 + -12y) = 3(6y + -6)

Reorder the terms:
-8 + -12y = 3(-6 + 6y)
-8 + -12y = (-6 * 3 + 6y * 3)
-8 + -12y = (-18 + 18y)

Solving
-8 + -12y = -18 + 18y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-18y' to each side of the equation.
-8 + -12y + -18y = -18 + 18y + -18y

Combine like terms: -12y + -18y = -30y
-8 + -30y = -18 + 18y + -18y

Combine like terms: 18y + -18y = 0
-8 + -30y = -18 + 0
-8 + -30y = -18

Add '8' to each side of the equation.
-8 + 8 + -30y = -18 + 8

Combine like terms: -8 + 8 = 0
0 + -30y = -18 + 8
-30y = -18 + 8

Combine like terms: -18 + 8 = -10
-30y = -10

Divide each side by '-30'.
y = 0.3333333333

Simplifying
y = 0.3333333333

See similar equations:

| -3(x+5)=52(x+5) | | 3(y-3)=4(y+3) | | 92=5w-8 | | 2x-67+x-11+3x= | | y=-1.636+0.793(3.2)+0.004(550)-0.0009(590)+0.009(65) | | 5y-18=6x+4 | | x^(-2/3)=1/36 | | 6x+x=80 | | y=90+4(x) | | y(x)=10x-140 | | 2x^4-18x^2+40=0 | | y(x)=10-140 | | 60=7x | | g/2.78=9 | | 14y^2-29y+2=0 | | 2(7-8)=32-10x | | 3z-2.5-5=x+17 | | 2x-67+x-23= | | 3-(3b-7)=43 | | x^3-12=-39 | | 9w-6=57 | | -8x+11=2x-9 | | r/2.4=7.5 | | 3.6=t/6.25 | | 7a-3=14-4n | | x^4-9x^2+6=0 | | y^2-40+80=0 | | 30x^2-6x^4= | | Y/5-7=4 | | 9u^2-25=0 | | 2/3-(7/4u)=-6/5 | | 6x=1x+-110 |

Equations solver categories